The effect of green tea extract on the sperm parameters and histological changes of testis in rats exposed to para-nonylphenol - Parisa Azizi M.Sc; Malek Soleimani Mehranjani Ph.D (Shahid Sadoughi University of Medical Sciences, 2019)
Background Para-nonylphenol (p-NP), an environmental contaminant, can generate free radicals that disturbs the reproductive properties. Green tea extract (GTE) is an antioxidant which may prevent the adverse effects of free radicals. Objective: The aim was to investigate the effect of GTE on sperm parameters and testis tissue in p-NP-treated rats. Materials and Methods 24 adult male Wistar rats (215 ± 20 gr) were randomly divided into four groups (n = 6/each) - including control, p-NP (200 mg/kg/day), GTE (200 mg/kg/day), and p-NP + GTE - and orally treated for 56 days. The right testes and left caudal epididymis were used to evaluate selected parameters. In addition, the concentration of serum malondialdehyde was calculated. Results A significant decrease in the sperm number, motility, viability and morphology (p < 0.001) was observed in the rats treated with p-NP compared to the control ones. The diameter of seminiferous tubules (p < 0.001), thickness of germinal epithelium (p = 0.018), total volume of testis (p = 0.009), volume of seminiferous tubules (p < 0.001), and testis weight (p = 0.017) decreased in the p-NP group in contrast with the other groups. Moreover, a significant increase of the malondialdehyde concentration was seen in the p-NP group when compared with the controls (p = 0.043). The majority of adverse effects of p-NP could be recovered following the administration of GTE. Conclusion It seems GTE can be used as a potent antioxidant in the case of p-NP toxication.